Ka-band miniaturized airtight wideband power amplifier - Zhao Peng; Li Kai; Hu Shunyong; Zhang Nengbo (Dianzi Jishu Yingyong)
This paper introduces an engineering realization of a Ka-band miniaturized airtight wideband power amplifier. Using 16 GaN power chips and 1 GaAs driver chip, the power is synthesized by combining a microstrip ring power divider/combiner with waveguide power divider/combiner and synthesizer network. The continuous wave saturated output power at 25~31 GHz is greater than 140 W. The power amplifier uses a forced air cooling solution with a finned heat sink, which improves the heat sink’s heat dissipation efficiency and provides good heat dissipation performance. The technical condition of the power amplifier is stable, its reliability and practicality meet the requirements for engineering use, and it is suitable for microwave transmission systems in field such as telemetry, communication, and electronic warfare.